Linear Cryptanalysis of S-Box BRADG - Oudha Oraby, Emaan; A.K. Albermany, Salah (International Journal of Engineering and Technology, 2018)
Block cipher reaction automata direct graph (BRADG) is used in protection wireless networks. BRADG processes data blocks of B bits with key length of B bits and given ciphertext of size B bits, where B is 64,128,512,...bits. BRADG is a faster and more efficient way to encrypt large data compared with the previous design of block cipher. In this thesis, the researcher presented a study to attack for BRADG algorithm by using linear cryptanalysis technique, by known-plaintexts and corresponding of the ciphertexts. As the results, it's possible to break: one bit in subkey 1-state BRADG cipher with at least 2 to power 3known-plaintext, and 16 bits subkey 1-state BRADG cipher with 2 to power 24 known plaintexts. The success rate of each attack is 84% , 92% ,97% and 99% depending on the number of known plaintext and the probability that the equation of the best approximation holds.